Effectiveness of agricultural development training program: the cases of teff and livestock farmers of Alaba Woreda, Southern Ethiopia - Surur, O.O. (Haramaya University, 2007)
This study intended to examine the effectiveness of teff and poultry farmers’ training process and outcomes in Alaba woreda. It was conducted, in four kebeles, through survey and qualitative method. The survey was undertaken on randomly selected trained and untrained teff and poultry farmers. The qualitative methods that were used at community, organizational and individual levels include: document review, focused/group discussion, personal interviews, and direct observation, and different tools such as, SWOT/force-field analysis, ranking, scoring, and rating. The data that are related with the training, context, process, changes in performances, and outcomes were collected and analyzed qualitatively and through descriptive analytical statistics and the chi-square. The results of the study revealed that: the gaps between the contents of the trainings and the identified needs of farmers were very wide because of lack of participatory need assessment. Training plan is based on quota from above; expected changes in performances are not indicated in the objectives, thus they are vague, incompatible and difficult to measure. Topics are very general and shallow, not thoroughly touching the prior needs of the farmers. Mostly, the training mix is more of theory and few practical, non interactive long lecture (talk) being one of the most commonly used methods. The urgency of trainings makes selection of participants "urgent" and creates unfair nomination, which is also affected by ‘informal’ criteria (personal relations and political outlook) and gender related biases. Conveniences of farmers in the arrangements of time and places of trainings are not considered genuinely and thus trainings can be under taken at peak cropping periods outside of their kebeles. These make the participation of women difficult and/or impossible, because of their multiple responsibilities. Thus, most of the trainings are male-biased. The group size is too large, and participation of farmers is very passive. Monitoring and evaluation of trainings did not exist and measurements of participant's reactions, learning, changes in on-the-job performances and outcomes of trainings have not been undertaken systematically. Farmers responses indicate, differences in KS among trained and untrained farmers have been observed only in few job tasks. Although it is difficult to give the actual changes directly brought by trainings, majority of the farmers in the study indicated that there is change in productivity of teff and poultry, because of the improved variety and exotic breeds, respectively. The study also revealed that, change agents’ trainings process was defective in planning, implementation, monitoring and evaluation aspects.Thus, to effectively implement participatory performance-based trainings, that are related with the actual work situations of the clients and that are aimed at achievable learning objectives: improvements through joint or participatory (bottomup) planning, effective implementation, follow-up and evaluation activities must be considered starting from farmers/FTCs level. Inclusion of training activities properly in the performance appraisal and evaluation system of the organization, with relevant performance measurement indicators; building capacity of the stakeholders in participatory planning, implementation monitoring and evaluation activities of the rural development and extension activities as a whole and in participatory training methodology (PTM) in particular; gradual implementation of the FTCs, i.e., starting with small number to learn from and to build on the experiences obtained, and in general shifting the approach to participatory methodologies are among the recommended way outs.